Indexes to Debates of the House of Assembly (Hansard) - South Africa Parliament, House of Assembly (Cape Town Government Printers, 1978)
South Africa. Parliament. House of Assembly. Debates of the House of Assembly (Hansard). Debates of Standing Committees.
South Africa Parliament House of Assembly Debates. Debates of Standing Committees published annually and parallel with Afrikaans title. Merged with: Debates of the House of Delegates, and Debates of the House of Representatives, to form: Debates of Parliament. 139 v. 22 cm.
Keywords: Indexes to Debates; House of Assembly; Hansard; First Session; Sixth Parliament; 27 January; 16 June; Vol. 77; ISBN 0621043907; JC045371; Index to Questions